2010
DOI: 10.1007/s11033-010-0413-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress elevated DNA damage and homocysteine level in normal pregnant women in a segment of Pakistani population

Abstract: Maternal oxidative stress during pregnancy may impair fetal growth and help in the development of diseases in adulthood. The aim of current study was to assess total oxidation status (TOS), related parameters and their relationship to DNA damage (%) and homocysteine level in normal pregnant women in low-income participants. In a cross-sectional study healthy women were grouped as normal, while age matched nulliparous and singleton pregnancies were included for first, second and third trimester groups. TOS (P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…Further, it has been proposed that oxidative stress provokes the release of sFlt-1 to a similar or greater extent than hypoxia [37]. Various longitudinal studies have shown increasing oxidative stress during pregnancy [38], [39], [40]. We have earlier reported a positive association between oxidative stress and sFlt-1 in preeclampsia [8].…”
Section: Discussionmentioning
confidence: 77%
“…Further, it has been proposed that oxidative stress provokes the release of sFlt-1 to a similar or greater extent than hypoxia [37]. Various longitudinal studies have shown increasing oxidative stress during pregnancy [38], [39], [40]. We have earlier reported a positive association between oxidative stress and sFlt-1 in preeclampsia [8].…”
Section: Discussionmentioning
confidence: 77%
“…Obesity is characterized by the, adipocyte hypertrophy, elevated production of reactive oxygen species, cytokines, chronic inflammation, disturbances in insulin and glucose metabolism [16][17][18]. Association between the occurrence of DNA lesions and enhanced body weight has been also reported [19][20][21]. Both inflammation and metabolic disturbances can cause DNA damage [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…41,42 Moreover, total oxidation status increases Hcy levels, and is known to generate reactive oxygen species such as H 2 O 2 . Accordingly, it has been proposed that elevated Hcy concentration causes endothelial dysfunction; thus, women who have hyperhomocysteinemia may be likely to experience endothelial dysfunction in the placental vasculature, 13,43 which may also have an effect on offspring cardiometabolic health via intrauterine mechanisms. 44 Elevated Hcy is known to be a modifiable risk factor due to the involvement of vitamin B12 and folate in the transmethylation to methionine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress increases DNA damage. 13 In a pilot randomized controlled trial of pregnant women 14 , continued supplementation with 400 μg folate/d in the 2 nd and 3 rd trimesters increased maternal and cord blood folate status, and prevented the increase in Hcy concentration in late pregnancy. However, there is little clinical and epidemiological evidence about whether maternal Hcy concentrations during pregnancyparticularly in the 3 rd trimester -can influence childhood health outcomes.…”
Section: Introductionmentioning
confidence: 99%